Abandono familiar y el estado emocional de un adulto mayor de 74 años del Cantón Caluma - Montalvo Tualombo, Fernanda Marisol (2023)
The present research aims to analyze the impact of family abandonment on the emotional state of adults over 74 years of age in the Caluma canton. To carry out this analysis, a conceptual framework will be used, encompassing the main emotional areas affected by this issue, through the application of psychological assessments using standardized clinical instruments. Furthermore, it seeks to determine the existing relationship between family abandonment and the emotional state of the adults under study. The results of this research were obtained through various psychological techniques and tools, including the review of clinical histories, clinical observation, clinical interviews, and the use of psychological reagents such as the Yesavage Geriatric Depression Scale. The results obtained in this research align with the theory presented in this case study, allowing us to reach significant conclusions that confirm the relationship between family abandonment and the emotional state of older adults in Caluma. These conclusions are essential to provide the necessary guidelines to establish a therapeutic intervention scheme that addresses the symptoms present in this vulnerable population.